2012
DOI: 10.5194/acp-12-769-2012
|View full text |Cite
|
Sign up to set email alerts
|

Possible effect of extreme solar energetic particle event of 20 January 2005 on polar stratospheric aerosols: direct observational evidence

Abstract: Abstract. Energetic cosmic rays are the main source of ionization of the low-middle atmosphere, leading to associated changes in atmospheric properties. Via the hypothetical influence of ionization on aerosol growth and facilitated formation of clouds, this may be an important indirect link relating solar variability to climate. This effect is highly debated, however, since the proposed theoretical mechanisms still remain illusive and qualitative, and observational evidence is inconclusive and controversial. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…We conclude that the present results show variations of the aerosol optical and microphysical parameters (in the cold polar stratosphere) that are similar to the aerosol variations detected after the GLE in January 2005 (Mironova et al, 2012). The recognized effect, during these two GLEs (20 January 2005 and29 September 1989), is found at the same altitude range of 10-20 km.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We conclude that the present results show variations of the aerosol optical and microphysical parameters (in the cold polar stratosphere) that are similar to the aerosol variations detected after the GLE in January 2005 (Mironova et al, 2012). The recognized effect, during these two GLEs (20 January 2005 and29 September 1989), is found at the same altitude range of 10-20 km.…”
Section: Discussionsupporting
confidence: 67%
“…Previous phenomenological studies (Mironova et al, 2008(Mironova et al, , 2012 yielded that there is a small, marginally detectable effect of an extreme SEP (e.g., such as the one of 20 January 2005) on the aerosol particles in the lower-middle polar stratosphere during stable winter/summer conditions. However, an appropriate model able to explain the observed features is still missing.…”
Section: A Mironova and I G Usoskin: Effect Of Ground Level Enhmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, empirical evidence has been produced for a possible effect of the ionization associated with an extreme SEP event on stratospheric aerosols (Mironova et al, 2012a). Significant simultaneous changes in aerosol properties were found in the polar stratosphere (11-25 km) of both hemispheres.…”
Section: The Veretenenko Effectmentioning
confidence: 99%
“…Mironova et al [19] observed an increase in the stratospheric aerosol production in a limited region of the Northern hemisphere a few days after the large ground level event (GLE) of 20 January 2005. However, the observed effect is at too high an altitude to influence the climate.…”
Section: Other Searches For the Influence Of Ionization On Cloud Formmentioning
confidence: 99%